2007
DOI: 10.1242/jeb.003913
|View full text |Cite
|
Sign up to set email alerts
|

Muscle strain is modulated more with running slope than speed in wild turkey knee and hip extensors

Abstract: . The consistent patterns of strain changes with running slope are evidence that strain pattern is modulated to meet the changes in demand for net mechanical work. The relatively poor relationship between strain and running speed may reflect the fact that changes in running speed during level running are not associated with a change in demand for net mechanical work. Taken together, the speed and slope results suggest that the demand for mechanical work is an important determinant of muscle length patterns in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 23 publications
(38 reference statements)
3
35
1
Order By: Relevance
“…The lengthening in early stance is related to knee flexion (Carr et al, 2011b), and shortening corresponds to a period of both knee extension and hip extension (Carr et al, 2011b). The overall strain cycle of the active ILPO found in the present study, taking into consideration regional strain, was qualitatively similar to previous studies of this muscle in guinea fowl and turkeys using a single segment length (Buchanan, 1999;McGowan et al, 2006;Roberts et al, 2007), and quantitative differences can probably be explained by differences in regional strain (Carr et al, 2011a). Buchanan (Buchanan, 1999) and McGowan et al (McGowan et al, 2006) reported larger strains than those found in the present study, probably because strain was estimated using measurements in the central to distal portions of the posterior fascicles (Carr et al, 2011a).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The lengthening in early stance is related to knee flexion (Carr et al, 2011b), and shortening corresponds to a period of both knee extension and hip extension (Carr et al, 2011b). The overall strain cycle of the active ILPO found in the present study, taking into consideration regional strain, was qualitatively similar to previous studies of this muscle in guinea fowl and turkeys using a single segment length (Buchanan, 1999;McGowan et al, 2006;Roberts et al, 2007), and quantitative differences can probably be explained by differences in regional strain (Carr et al, 2011a). Buchanan (Buchanan, 1999) and McGowan et al (McGowan et al, 2006) reported larger strains than those found in the present study, probably because strain was estimated using measurements in the central to distal portions of the posterior fascicles (Carr et al, 2011a).…”
Section: Discussionsupporting
confidence: 87%
“…Buchanan (Buchanan, 1999) and McGowan et al (McGowan et al, 2006) reported larger strains than those found in the present study, probably because strain was estimated using measurements in the central to distal portions of the posterior fascicles (Carr et al, 2011a). The larger strains found in the ILPO of turkeys (Roberts et al, 2007) may have a similar cause, although a species difference cannot be ruled out. Similar to the ILPO in guinea fowl, the ILPO of turkeys shows increased shortening and decreased lengthening when the birds run uphill.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Note that the stance active ILPO can itself be considered a neuromuscular compartment of the iliotibialis lateralis because in most species it is contiguous with the iliotibialis lateralis preacetabularis, which is active during swing phase (Gatesy, 1999b). Whether further differences in function occur along the anterior-posterior axis within the ILPO has not been revealed in previous studies (Buchanan, 1999;McGowan et al, 2006;Roberts et al, 2007).…”
Section: Introductionmentioning
confidence: 96%